Health Behaviors of Childhood Cancer Survivors - Jennifer S. Ford; Marie Barnett; Rachel Werk (MDPI AG, 2014)
There has been a dramatic increase in the number of childhood cancer survivors living to an old age due to improved cancer treatments. However, these survivors are at risk of numerous late effects as a result of their cancer therapy. Engaging in protective health behaviors and limiting health damaging behaviors are vitally important for these survivors given their increased risks. We reviewed the literature on childhood cancer survivors' health behaviors by searching for published data and conference proceedings. We examine the prevalence of a variety of health behaviors among childhood cancer survivors, identify significant risk factors, and describe health behavior interventions for survivors.